Administration of Moringa Leaf Extract to Reduce Oxidative Stress and Increase Fertility of Diabetes Melitus Mice (Mus Muculus - Zul Hendry; Henny Yolanda; Marthilda Suprayitna (GLOBAL HEALTH SCIENCE GROUP, 2024)
The impact of diabetes mellitus on decreased male fertility or infertility will greatly reduce the quality of life. Therefore, it is necessary to conduct research on the prevention and treatment of decreased fertility experienced by diabetes mellitus patients, including by utilizing local naturalingredients. Objective: The aim of this study is to determine the effect of moringa to reduce Oxidative Stress and increase Fertility of Diabetes Mellitus Mice. Method: Randomized Posttest Control Group design with 35 mice (Mus Musculus) as respondents which were divided into 5 groups randomly. Results: Moringa leaf extract can significantly reduce MDA levels in diabetic mice given moringa extract at doses of 200 and 300 mg/kgbb Conclusions: Moringa leaf extract can reduce Oxidative Stress and increase Fertility of Diabetes Mellitus Mice.